Forest and connectivity loss drive changes in movement behavior of bird species - Ramos, Danielle Leal [UNESP] (2020)
In a rapidly changing world, it is important to understand how environmental modifications by humans affect species behavior. This is not a simple task, since we need to deal with a multitude of species and the different external contexts that affect their behavior. Here, we investigate how interpatch short-distance movements of 73 common forest bird species can be predicted by forest cover and forest isolation. We modeled bird movement as a function of environmental covariates, species traits – body mass and feeding habit – and phylogenetic relationships using Joint Species Movement Models. We used field data collected in forest edges and open pastures of six 600 × 600 m plots in the Atlantic Forest biodiversity hotspot. We found that birds fly larger distances and visit more forest patches and remnant trees with decreasing forest cover. Increasing landscape isolation results in larger flight distances, and it increases the use of trees as stepping-stones for most species. Our results show that birds can adjust their behavior as a response to spatial modification in resource distribution and landscape connectivity. These adjusted behaviors can potentially contribute to ecosystem responses to habitat modification.